Estimation of aboveground tree biomass Toona sureni and Coffea arabica in agroforestry system of Simalungun, North Sumatra, Indonesia - SITI LATIFAH; MUHDI MUHDI; AGUS PURWOKO; ETIKA TANJUNG (Society for Indonesian Biodiversity, 2018)
Latifah S, Muhdi, Purwoko A, Tanjung E. 2018. Estimation of aboveground tree biomass Toona sureni and Coffea arabica in agroforestry system of Simalungun, North Sumatra, Indonesia. Biodiversitas 19: 670-675. Agroforestry is an ecologically and environmentally sustainable land use that offers great promise to carbon (C) sequestration. Forests play a significant role in reducing greenhouse gas emissions through maintaining current carbon stores and by increasing the rate of carbon sequestration. Vegetation carbon stocks are necessary to be quantified to evaluate the carbon sequestration potential in the ecosystem. Reasonable methods for estimating tree biomass and carbon storage on forest land are increasingly crucial given concerns of global climate change. This study aimed to evaluate C sequestration potential by agroforestry in North Sumatra Indonesia. This study was conducted at the Agroforestry system in Aek Nauli, Simalungun District, North Sumatra. Data collection for primary data was done through a field survey. The present study was carried out to determine above ground tree biomass of Toona sureni (Blume) Merr and Coffea arabica. Data retrieval of T. sureni and C. arabica was done by non-destructive sampling by measuring the diameter at breast height (dbh). The results showed that the potential of average above-ground biomass and carbon storage of T. sureni and C. arabica was 6.25 t ha-1 and 2.88 C t ha-1, respectively. Total aboveground biomass of Toona sureni and C. arabica in the study area was 93.75 ton, while total of carbon storage was 43.16 ton